Biodiversity and Development Co-operation - Drutschinin, Anna (OECD Development Co-operation Working Papers, 2015)
This paper considers how development co-operation is addressing the twin objectives of biodiversity conservation and sustainable use on the one hand, and development and poverty reduction on the other. It outlines how development co-operation can a) support mainstreaming biodiversity and ecosystem services into development; b) manage for results, particularly across trade-offs and synergies; c) incorporate monitoring and evaluating approaches into biodiversity-related development co-operation activities; and d) better align and harmonise providers' activities with partner country priorities. The paper showcases examples of how development co-operation is supporting conservation and sustainable use of biodiversity and ecosystem services. It also identifies areas where more research is needed, such as sharing experience with the tools and good practices available for successful mainstreaming, and developing indicators to improve monitoring and evaluation to boost understanding of the effectiveness of biodiversity-related development interventions and of the relative performance of different mainstreaming approaches